PENGGUNAAN DRONE OLEH PEMBERONTAK HOUTHI DALAM PENYERANGAN KILANG MINYAK ARAB SAUDI MENURUT HUKUM UDARA: The Use of Drones by Houthis Rebel in the Attack on Saudi Arabia Oil Refinery according to Air Law - Muhammad Fikri Ridwansyah; Sugeng Supartono (Reformasi Hukum Trisakti, 2025)
State sovereignty over airspace according to international law is intact and full. International regulations or conventions have not expressly regulated unmanned aircraft (drones). The development of drone regulation is developing very slowly because there are no laws and standards set by the International Civil Aviation Organization (ICAO) in the use of drones. The problems of this research are: how is the legality of drones in crossing state borders and how is Yemen responsible for the actions of Houthi rebels? This type of research uses a normative juridical method, a descriptive, uses secondary data, data is analyzed qualitatively, and conclusions are deductive. The results and conclusion of this study indicate that the regulation of drones is equated with aircraft. Still, the mention of drones has not been specifically regulated in national and international air law. The regulation on this matter is only limited to the conventions and recommendations of the ICAO. Then, Yemen is not responsible for the actions of the Houthi group even though the group has adopted Yemen and claimed to be the country's national movement. It is because Yemen does not recognize the group as an organ of the state.